2015
DOI: 10.1083/jcb.201506102
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress–dependent phosphorylation activates ZNRF1 to induce neuronal/axonal degeneration

Abstract: Oxidative stress induces EGFR-dependent phosphorylation and activation of ZNRF1 ubiquitin ligase in neurons, which promotes two major neurodegenerative pathways, apoptosis and axonal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 47 publications
4
48
0
Order By: Relevance
“…We recently showed that ROS generated by NADPH oxidases serve as an intracellular signaling mediator after axonal injury in order to promote Wallerian degeneration by inducing EGFR-dependent ZNRF1 phosphorylation. 8 These findings combined with the present results suggest that the NADPH oxidase family of molecules play a more significant role in initiating neuronal degeneration than previously expected. NADPH oxidases accelerate apoptosis even when cell death is induced by an exogenously applied oxidant, suggesting that ROS generated by NADPH oxidases, which are closely located to the protein machineries that promote apoptosis, including those of ZNRF1 and EGFR, are more relevant for initiating neuronal degeneration than ROS generated elsewhere.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…We recently showed that ROS generated by NADPH oxidases serve as an intracellular signaling mediator after axonal injury in order to promote Wallerian degeneration by inducing EGFR-dependent ZNRF1 phosphorylation. 8 These findings combined with the present results suggest that the NADPH oxidase family of molecules play a more significant role in initiating neuronal degeneration than previously expected. NADPH oxidases accelerate apoptosis even when cell death is induced by an exogenously applied oxidant, suggesting that ROS generated by NADPH oxidases, which are closely located to the protein machineries that promote apoptosis, including those of ZNRF1 and EGFR, are more relevant for initiating neuronal degeneration than ROS generated elsewhere.…”
supporting
confidence: 81%
“…They were then washed, cultured in Neuro-medium containing 2% Neuro-Brew-21 and 1 mM glutamine for 24 h, and used in immunoblotting or immunostaining experiments. The antibodies used were as follows: anti-ZNRF1 antiserum; 7,10 antiserum for phosphorylated ZNRF1 at Y103; 8 rabbit anti-caspase 3 and anti-cleaved caspase 3 antibodies (9662, 9661, Cell Signaling Technology); rabbit polyclonal anti-βIII-tubulin antibody (Poly18020, BioLegend); anti-β-actin antibody (622101, BioLegend).
Figure 1.
…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations